Rozwój infrastruktury technicznej w latach 2004-2014 jako czynnik zrównoważonego rozwoju gmin Kampinoskiego Parku Narodowego = The development of technical infrastructure between 2004-2014 as a factor of a sustainable development of the municipalities of Kampinoski National Park - Podawca, Konrad; Karsznia, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article describes the changes that have taken place over 11 years in the development of technical infrastructure of the Kampinoski National Park (KPN) municipalities. The availability of waterworks and wastewater systems is important both in the context of health protection as well as for the preservation of unique natural values of KPN. Regarding that, a multifactoral analysis was performed for the time period 2004-2014 by increments of 5 years, ex. for 2004, 2009, 2014 etc. with the use of statistic data provided by Central Statistical Office of Poland (GUS) in the Local Data Base (BDL).
Keywords: gmina; infrastruktura wodociągowo-kanalizacyjna; park narodowy; zrównoważony rozwój; planowanie przestrzenne; municipality; waterworks; wastewater system; national park; sustainable development; spatial planning; Kampinoski Park Narodowy